Effectiveness of ABPK as a decision-making tool in choosing the right contraception for new acceptors at TPMB Nur Handayani in 2024 - Yanuarti, Tuty; Handayani, Nur; Yazidah, Izzatul; Lishanawati, Rd. Emilia; Yani, Sanda Ummu Lutfi Ahk; Saputra, Novitasari; Larasati, Woro; Novita, Novita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Indonesia, with amount resident reached 281.603 million souls in 2024, ranked fourth world. As a developing country, Indonesia faces challenge big related growth residents who still high. For control birth, especially post childbirth, planning family through contraception becomes important. Use contraception post labor can lower number death mother (AKI) and increase amount new KB acceptor, which is objective main family program planning in Indonesia. For evaluating effectiveness of ABPK as tool taking decision in choose appropriate contraception in acceptors new at TPMB Nur Handayani Year 2024. This research use Quasi Experiment with Two Group Pre-test Post-test Design. The sample consists of 40 selected respondents with technique total sampling. Data analysis using the Wilcoxon Signed Rank Test statistical test. The results of the study show that Group A using ABPK has the average value (mean) is 10.50 with Z score -3.963b and P-Value 0.001. Group B, which does not using ABPK has the same average value, but with Z score -4.234b and P-Value 0.001. These results show that ABPK is more effective in help acceptor choose proper contraception compared to without ABPK ABPK proven effective as tool help taking decision in choose appropriate contraception in acceptors new at TPMB Nur Handayani 2024. It is expected public can utilize ABPK for make more decisions appropriate in choose contraception, which in turn support success of family program planning.